Kajian Potensi Air Kali Bekasi untuk Penyediaan Air Baku - Suhardi - (Universitas Islam 45, 2020)
Rapid development in Bekasi City, Indonesia, requires the support of adequate facilities and infrastructure, including the availability of raw water. Raw water potential for Bekasi City is very limited. Therefore, this study aims to examine the potential of Bekasi River as a source of raw water for Bekasi City. Therefore, this study aims to examine the potential of Bekasi River as a source of raw water for Bekasi City. Research methodologies include secondary data collection, water availability analysis using dependable flow (weibull method), water demand analysis, water balance analysis (water balance), storage capacity analysis, water quality analysis. Result showed that Bekasi River water is not enough in quantity to meet the raw water needs for Bekasi City. Water balance showed that in 2024 there will be a lack of water for the scenarios Q50, Q80, and especially in Q90. In order to meet the water need in Bekasi City, water reservoir engineering is needed with a storage volume of 176 million m3. Bekasi River water does not meet class 1 quality standards in terms of quality, so efforts are needed to control water pollution in the Bekasi River.